Growth and Biomass in Response to Salinity and Subsequent Fresh Water in Mangrove Seedlings Avicennia marina and Rhizophora stylosa - Mohammad Basyuni; Lollie Agustina Pancawaraswati Putri; Berliana Nainggolan; Putri Ester Sihaloho (Jurnal Manajemen Hutan Tropika, 2014)
The present study describes the growth and biomass of salt secretor mangrove, Avicennia marina and the non-secretor Rhizophora stylosa by long-term exposure to salinity and its subsequent fresh water. The seedlings of the 2 mangroves grown with varying salt concentration for 3 months were then divided into 2 treatment groups, and grown for another 3 months: 1 continuously in salinity conditions and another in fresh water to recover from salinity. The growth parameter namely plant height and diameter of A. marina was significantly enhanced by salt with maximal stimulation at 2% (equal to 75% natural seawater) and this increase appeared to be attenuated by increasing the salinity concentration above 2%. By contrast, the growth of R. stylosa significantly thrived up to 0.5% salt concentration, then decreased with the increasing of salinity. The growth of both species slightly increased after removal to salinity. Our findings suggested that within the range of salinity treatments, A. marina was more salt tolerant than R. stylosa, which provides important information for mangrove rehabilitation in North Sumatra. The biomass of the 2 mangrove seedlings was changed in the same manner as the growth of plants upon salt and fresh water treatment. These results suggested the importance of mangrove adaptation withstand salt and/or water stress.